The development of ambitious instruction: How beginning elementary teachers' preparation experiences are associated with their mathematics and English language arts instructional practices. (February 2022) - Youngs, Peter; Elreda, Lauren Molloy; Anagnostopoulos, Dorothea; Cohen, Julie; Drake, Corey; Konstantopoulos, Spyros
Abstract: This study of 83 graduates from 5 elementary teacher education programs found that elementary candidates' opportunities to learn general teaching methods were positively associated with their enactment as first-year teachers of ambitious mathematics and English language arts (ELA) practices. Opportunities to practice content-specific instructional strategies during student teaching were positively associated with first-year teachers' enactment of ambitious mathematics practices, but negatively associated with classroom management in mathematics and disciplinary demand in ELA. First-year teachers' classroom management was positively associated with enactment of ambitious instruction in both subjects. In sum, we identify several learning opportunities that support first-year teachers' ambitious instruction. Highlights: This study followed 83 elementary candidates through their first year of teaching. We investigated learning opportunities in pre-service courses and student teaching. We examined first-year teachers' enactment of ambitious mathematics and ELA instruction. We used PLATO to assess enactment of ambitious instruction in both subjects.